A study of nutritional status and personal hygiene among adolescent girls of rural Bikaner - Vyas, B. L.; Sethia, Renu; Acharya, Rekha (International Journal Of Community Medicine And Public Health, 2017)
Background: Adolescent girls form an important vulnerable sector of population that constitute about one tenth of Indian population. Methods: The study was conducted at Udairamsar village at Bikaner which is the field practice area of Department of Community Medicine, S.P. Medical College, Bikaner. Results: Out of 489 girls, 436 were Hindu. 73.21% girls were living in nuclear family and 60.32% girls belonged to socio-economic status IV. Out of 489 girls, 46.42% girls were anaemic and 2.04% girls were having vitamin–B deficiency. Conclusions: Anaemia was common problem among adolescent girls in rural area. The personal hygiene was good among adolescent girls.